(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2021)
One of the leading sectors of the economy of Kazakhstan is oil production and refining. Pollution with oil and oil products can lead to modern changes in the human environment, disruption of the natural balance of micronutrients in the biosphere. An industrial enterprise, especially an enterprise of the first class of hazard, uses modern environmental technologies. No matter how much these companies invest in reducing emissions of pollutants into the environment, they affect and pollute all components of the environment, negatively affecting the health of the local population. Oil pollution can lead to significant changes in the ecological environment of a person. Atyrau region occupies a special place among the zones of ecological disaster in Kazakhstan. The ecological situation here is formed under the influence of natural and anthropogenic factors, the most important of which are the rise of the Caspian Sea and the rapid development of the oil and gas industry. A rise in sea level can lead to the death of plants in shallow water, as well as to the formation of zones of contamination with hydrogen sulfide as a result of the flooding of existing oil and gas fields, the territory of which is contaminated with oil products. Monitoring studies indicate that long-term oil production and an annual increase in emissions and discharges of the Atyrau Refinery, GPP into the environment has led to a significant increase in the level of oil and oil products, including hydrogen sulfide in the soil. The more oil and oil products in waste wa- ter, and the more H2S. To determine the environmental assessment of the impact of oil pollution on the environment, the coastal soils were taken from the evaporation field of the Atyrau refinery wastewater. The results of the work can be used to improve the ecological state of the region, health and well-being of the population. Key words: evaporation, oil waste, hydrogen sulfide, pollution, soil, waste water.